Optimization of agrobacterium-mediated transformation protocol for Malaysian rice (Oryza Sativa L.) Cultivar MR219 using shoot apices as target tissue - Clement, Wong Kiing Fook (2015)
Optimization of the Agrobacterium-mediated transformation protocol of rice has always been the fundamental behind all transgenic research before the insertion of any gene of interest. After all, an optimized protocol often translates into improved transformation efficiency. Rice calli was the most preferred target tissue since optimization studies using this explant were more established. Nonetheless, rice shoot apices derived from germinated seedlings has proven to be a better target tissue since it by-pass lengthy and frequent subculturing and regeneration steps. The first part of the study was to investigate the explants ability to form in-vitro multiple shoots by using three cytokinins – KIN, BAP and TDZ. Optimal concentration of 4 mg/l of TDZ produced the most shoots (6.75),followed by 4 mg/l of KIN (5.50) and 3 mg/l BAP (5.25). The biochemical changes of the in-vitro shoots grown at optimal concentrations of cytokinins indicated that in-vitro shoots produced in KIN contain the highest total chlorophyll content (0.430 g/mg FW) as compared to BAP (0.223 g/mg FW) and TDZ (0.154 g/mg FW). TDZ-produced invitro shoots contain the highest total soluble sugar content (0.120 g/mg FW), followed by KIN (0.104 g/mg FW) and lastly, BAP (0.097 g/mg FW). There were no significance difference observed on the total soluble protein content of the in-vitro shoots cultured in all three cytokinins supplemented media. KIN was subsequently chosen as the suitable cytokinin due to its production of relatively high number of shoots and quality shoots with highest total chlorophyll content and moderately high total soluble sugar content. After four weeks of culturing in 4 mg/l of KIN, in-vitro shoots were successfully rooted for 2 weeks in 0, 0.5 and 1.0 mg/l of IBA. Hardened rice plants were acclimatized in the glasshouse with influorescence observed after two months. Minimal inhibitory concentration (MIC) of selected antibiotics and herbicide towards the growth of shoot apices was also determined. Aminoglycosidic antibiotics such as kanamycin,paromomycin and neomycin showed 100% survival of shoot apices at all tested concentrations of 0 to 500 mg/l. However, the MIC for another aminoglycosides – geneticin (G418) was determined at 300 mg/l with 52% of survived shoot apices. Hygromycin and basta proved to be better alternatives with relatively lower MIC recorded. At concentration of 20 mg/l hygromycin, the percentage survival was 8.5% whereas 8.0% of explant survival was determined at 9 mg/l of basta. The optimization of Agrobacterium-mediated transformation protocol showed that strain EHA101 (38.0%, 35.0%) and EHA105 (33.0%, 27.5%) presented higher transient GFP and GUS reporter genes expression respectively as compared to LBA4404 (15.0%, 22.5%). Shoot apices derived from four days old seedlings gave the highest GFP (35.0%) and GUS (33.5%). Additional wounding of the explant with needle (18.0%, 10.0%) and scalpel (13.0%, 18.0%) did not improve the expression of GFP and GUS comparing to excised shoot apices (33.0%, 47.5%). A 30 minutes bacterial immersion time (35.0%, 33.0%) and 72 hours of co-cultivation period (38.0%, 35.0%) gave the highest transient GFP and GUS expression. The application of heat treatment for 3 minutes in addition to 30 minutes of immersion time produced 63.0% and 42.5% of shoot apices transiently expressing GFP and GUS as compared to untreated explant (34.0% GFP, 36.25% GUS expressions). A series of phenolic compounds at 100 μM was evaluated for their ability in vir induction. Amongst tested phenolics which include cinnamic acid, coumaric acid and ferulic acid,vanillin (32.5% and 23.5%) was selected as a potential substitute for acetosyringone (37.5%, 28.8%) in terms of percentage plant expressing GFP and GUS. Optimal concentration of vanillin was also determined at 150 μM with 47.5% and 45.0% plants expressing GFP and GUS. Pre-treatment of explants with a combination of macerase, cellulase and pectinase before bacterial immersion produced 40.0% and 35.0% explants expressing GFP and GUS. Untreated explants and explants treated with individual enzymes did not yield high expression of both reporter genes. A 60 minutes of enzyme incubation period (37.5%, 35.0%) was optimal to achieve high GFP and GUS expression as compared to untreated explants (32.5%, 28.5%). Molecular PCR analyses showed that transformation efficiencies was improved when explants were treated with heat (15.83%),vanillin (17.50%), hydrolytic enzymes (16.67%) and a combination of the three treatments (10.00%) when compared to the normal transformation protocol (5.83%). To conclude, the use of shoot apices could reduce the time needed to produce transgenic rice with superior agronomic traits. Also, the improved transformation efficiency of this protocol will allow efficient production of transgenic rice.